Global trends in research of pseudomyxoma peritonei: a bibliometric and visualization analysis - Liu, Shuo; Liu, Xue; Ma, Ruiqing; Yu, Shuang; Lu, Liangyuan; Lin, Yanjun; Yang, Zhanmin (Frontiers in Oncology, 2024)
Pseudomyxoma peritonei (PMP) was a complex disease that had attracted increasing attention. However, there had been no bibliometric analysis of this disease so far. This study aimed to explore the current situation and frontier trend of PMP through bibliometric and visualization analysis, and to indicate new directions for future research.The original research articles and reviews related to the PMP research were downloaded from Web of Science Core Collection on September 11, 2023. CiteSpace (6.2.R4) and VOSviewer(1.6.18) were used to perform bibliometric analysis of the publications, and establish the knowledge map. The data collected was analyzed using the Online Analysis Platform of Bibliometric to evaluate the cooperation of countries in this field.We identified 1449 original articles and reviews on PMP published between 1998 and 2023. The number of publications on PMP increased continuously. The United States, the United Kingdom and China were the top contributors. The most productive organization was the MedStar Washington Hospital Center. Sugarbaker, Paul H. was the most prolific author and the most cited. Keyword analysis showed that "Pseudomyxoma peritonei", "cancer", "cytoreductive surgery", and "hyperthermic intraperitoneal chemotherapy" were the most common keywords. The earliest and latest used keywords were "mucinous tumors" and "impact", respectively. "classification", "cytoreductive surgery", "appendiceal" were the top 3 strongest citation bursts. The reference "Carr NJ, 2016, AM J SURG PATHOL" had the highest co-citations.This bibliometric analysis showed an increasing trend in literature related to PMP. The research trends and hotspots identified in this study could guide the future research directions in this field, in order to promote the development of PMP.